Beyond incommensurability: Jerusalem and Stockholm from an ordinary cities perspective. Issue 3 (3rd May 2016) - Rokem, Jonathan
Abstract : This paper's core argument is that we should start creating theories that encompass different cities and include them in a more flexible and relational comparative framework. This must include a new urban terminology which does not continue the all-too-fashionable labelling of cities on a continuum between first world and third world, global North-West and South-East or as I emphasize below, including what have been labelled extremely contested cities in a more flexible and relational ordinary cities framework. To introduce such a comparative approach, I will examine Jerusalem and Stockholm via three contrastive and relational patterns: institutional segregation ; urban violence ; and non-governmental organization involvement in planning . In so doing, I point towards the necessity to open up research on extreme urban conflicts, suggesting that when assessing specific contextual patterns, those labelled as extremely contested cities (such as Jerusalem) share more similarities with other more ordinary cities (represented by Stockholm) than was previously perceived, often stemming from ethnic, racial and class conflicts revolving around issues of politics, culture and identity, among others.